PEG vs. sennosides for opioid-induced constipation in cancer care. - Hawley, Philippa; MacKenzie, Hannah; Gobbo, Monica (Supportive Care in Cancer, 2020)
Purpose: This randomized double-blind, double-dummy, 2-treatment, 2-period crossover study aimed to compare the efficacy and tolerability of polyethylene glycol (PEG) and sennosides in ambulatory cancer patients with opioid-induced constipation.Methods: Outpatients ≥ 18 years old with cancer, at risk of or already experiencing opioid-induced constipation, were randomly assigned to begin a standard bowel protocol of escalating doses of sennosides or PEG, plus a dummy preparation. After 3 weeks, the patients switched to the alternate active product and dummy preparation. Constipation was assessed using the revised Victoria Bowel Performance Scale (rBPS) at the end of each of the 2 consecutive 21-day study periods for the number of days with a satisfactory bowel movement, the time in days to goal rBPS (G), and the treatment preference of each patient.Results: Seventy patients were recruited, with 42 completing their first treatment period and 28 completing both treatment periods. For the typical patient, the expected number of days with a satisfactory bowel movement per days of treatment was found to be 1.21 times higher on PEG than on sennosides in a particular period (95% credible interval 0.96 to 1.55). Patients taking PEG were 1.47 times more likely to reach a rBPS of G before patients taking sennosides in the first period (95% confidence interval 0.74 to 2.94). There was no evidence of a difference in patient preference between laxatives.Conclusion: Our study found weak evidence that PEG is superior to sennosides with respect to overall effectiveness in cancer patients with opioid-induced constipation.